2019
DOI: 10.4103/ijp.ijp_184_18
|View full text |Cite
|
Sign up to set email alerts
|

Curricular adequacy on basics of clinical trials

Abstract: INTRODUCTION: Clinical trials are integral to innovation in the treatment modalities and are conducted to assess the safety and efficacy of novel drugs. Clinical trials of modern era have evolved through stern consequences and tragedies in the past. This study was designed to know knowledge on ethics, adverse drug reactions (ADRs), and tragedies in clinical trials among interns and postgraduates (PGs). METHODOLOGY: A cross-sectional study was carried out on graduates un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
1
0
0
Order By: Relevance
“…[ 20 ] PG theses often report findings which are incomplete, inadequate and lack uniformity. [ 21 ] Like other researchers,[ 22 ] we have also observed that students do not have clear concepts regarding clinical trials. Outcome is often confused with results and interventional trials are labelled as observational along with mislabelling of trial phase.…”
Section: Discussionsupporting
confidence: 72%
“…[ 20 ] PG theses often report findings which are incomplete, inadequate and lack uniformity. [ 21 ] Like other researchers,[ 22 ] we have also observed that students do not have clear concepts regarding clinical trials. Outcome is often confused with results and interventional trials are labelled as observational along with mislabelling of trial phase.…”
Section: Discussionsupporting
confidence: 72%